PENGARUH INDEPENDENSI, TIME BUDGET PRESURE, DAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDIT ANGGARAN PENANGANAN COVID-19 (STUDI EMPIRIS PADA KANTOR BPKP PERWAKILAN MALUKU) - Lakussa, Silviya Mellvi; Engko, Cecilia; Batkunde, Adonia. A. (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study empirically examines the effect of independence, time budget pressure, and auditor professionalism on the quality of audits produced during the Covid-19 pandemic at BPKP Mollucas Representative. The sample in this study was 30 auditors who worked at BPKP Mollucas Province. The model was the same as the total population. Therefore it's a saturated sample (census). Data was collected through questionnaires entered at the Mollucas Province BPKP Office. The data was then analyzed using multiple linear regression analysis techniques with the help of SPSS 21 software. The study's results showed that independence has a significant positive effect on Audit Quality, time Budget Pressure does not affect Audit Quality, and auditor Professionalism has a significant positive effect on Audit Quality